Seed storage protein changes and mobilization pattern in Bambaranut (Vigna subterranea) (L.) Verdc. during germination - Saminu, Najib M; Muhammad, Yusuf Y (Plant Science Today, 2022)
The germination of seeds involves series of events during which mobilization and utilization of seed storage proteins occur. This study is aimed at determining the changes in total and fractions of seed storage protein in six bambaranut landraces during 96 hrs germination period. The study assessed the changes in seed storage protein content, storage protein profile, endopeptidase activity, free amino acids and gibberellic acid levels. Significant (p<0.05) decrease in total storage protein after 24 hrs, albumin from 48 hrs and globulin and glutelin after 72 hrs germination period were observed in the studied landraces. Prolamin showed significant (p<0.05) decrease after 48 hrs in all the landraces. Five peptide bands were detected in the six landraces with molecular weights corresponding to 97.4 kDa, 45 kDa, 29 kDa, 20.1 kDa and 18 kDa. Peptide bands with molecular weight of 97 kDa and 29 kDa decreased in intensity after 48 hrs of germination in four landraces. Free amino acids content significantly (p<0.05) increased following 24 hrs germination period in all the landraces. The activity of endopeptidase increased significantly (p<0.05), reaching maximum after 96 hrs germination. Significant (p<0.05) increase in gibberellic acid level throughout germination period was also observed. Although slow degradation rate of storage proteins was observed, there was variation in the rate at which storage protein and its fractions decreased among the bambaranut landraces during germination. This variation could be utilized towards obtaining improved bambaranut genotypes with better germination characteristics.